On condensed set in ideal topological spaces. Issue 5 (4th July 2022) - Abdalbaqi, Luma S.; Al-Swidi, Luay A.; Hadi, Mustafa Hasan
Abstract: The main pillar of the research is the definition of a new type of operator ϵ * : p ( k ) → p ( k ), and to study its relationship with density in ideal spaces. The second path depends on the definition of the topological compatibility with the ideal and its relationship to this operator. Finally we defined the new concept of kernel by using this operator.